Economic Growth and the Dynamics of Wage Determination: A Micro Simulation Study of the Stability Consequences of Deficient Variation in Factor Prices and Micro Structures - Gunnar Eliasson; Thomas Lindberg (The Research Institute of Industrial Economics (IUI), 1986)
Swedish Manufacturing Industry is said to be technologically and commercially in good shape. While Swedish wage levels were higher than in all industrial countries in the mid-70s, wages - expressed in international currencies - have now dropped to a mid-position, and real rates of return are back to the average for the postwar period. Given what empirical research on Swedish labor market behavior tells us, the large devaluation in late 1982 should have been followed by strong wage drift. However, to understand recruitment and wage setting decisions, one really needs a model in which firm pricing, production and investment decisions are controlled by overriding profitability objectives and where the rate of interest plays a role. The Swedish micro-to-macro model is such a model.
Keywords: J31; L10; L23; 330; Economic growth; wage setting; micro-macro simulation model; Lohntheorie; Theorie